PENGARUH MODEL BLENDED LEARNING BERBANTUAN VIDEO INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Vika Palera; Nurul Anriani; Cecep Anwar Hadi FS (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2019)
This research is a quasi-experimental study that aims to determine the effect of interactive video-assisted Blended Learning models on mathematical problem solving abilities. This research was conducted at SMPN 13 Serang City class VIII. The population in this study consisted of 10 classes VIII and taken 2 classes to be sampled. Sampling was done by cluster random sampling technique. The Blended Learning model used in this study isconventional learning in class by involving online resources and online activities which are not a requirement for students to follow. While the video used is a video adopted from one of the paid online learning rooms, Ruang Guru. Problem solving ability is measured using a test in the form of a valid and reliable question description. Furthermore, the data obtained were analyzed using quantitative descriptive analysis.